PENGARUH KUALITAS INFORMASI DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN MEREK PADA E-COMMERCE - Afandi, Mochammad Farid; Christian, Juan Berly; Indraningrat, Ketut; Destari, Fajar (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2025)
This study investigates the factors influencing online purchasing decisions among university students, with a particular emphasis on the roles of information quality and ease of use. It further examines trust as a mediating variable in the relationship between these factors and purchasing decisions. The rapid growth of online booking applications has shifted consumer behavior, particularly among younger demographics, making it essential to understand how current behavior may predict future trends. An explanatory research design was employed, targeting university students in East Java who had used online booking applications during the 2023–2024 period. Data were collected through an online questionnaire distributed using purposive sampling, resulting in 380 valid responses. The analysis was conducted using path analysis with the support of SPSS version 25.The results indicate that both information quality and ease of use significantly influence students' purchasing decisions through the mediating role of trust. These findings highlight the importance of building user trust to enhance the effectiveness of online booking platforms. The implications, limitations, and recommendations for future research are discussed in detail.